Regulation of Alpha-Secretase ADAM10 In vitro and In vivo: Genetic, Epigenetic, and Protein-Based Mechanisms - Endres, Kristina; Deller, Thomas (Frontiers in Molecular Neuroscience, 2017)
ADAM10 (A Disintegrin and Metalloproteinase 10) has been identified as the major physiological alpha-secretase in neurons, responsible for cleaving APP in a non-amyloidogenic manner. This cleavage results in the production of a neuroprotective APP-derived fragment, APPs-alpha, and an attenuated production of neurotoxic A-beta peptides. An increase in ADAM10 activity shifts the balance of APP processing towards APPs-alpha and protects the brain from amyloid deposition and disease. Thus, increasing ADAM10 activity has been proposed an attractive target for the treatment of neurodegenerative diseases and it appears to be timely to investigate the physiological mechanisms regulating ADAM10 expression. Therefore in this article, we will (1) review reports on the physiological regulation of ADAM10 at the transcriptional level, by epigenetic factors, miRNAs and/or protein interactions, (2) describe conditions, which change ADAM10 expression in vitro and in vivo, (3) report how neuronal ADAM10 expression may be regulated in humans, and (4) discuss how this knowledge on the physiological and pathophysiological regulation of ADAM10 may help to preserve or restore brain function.